Hubungan Kekerabatan Sapi Aceh dengan Menggunakan Daerah Displacement-loop - Abdullah, Mohd. Agus Nashri (Jurnal Agripet, 2008)
Relationship of aceh cattle using displacement-loop regionABSTRACT. The aims of this study were to describe relationship of D-loop of mtDNA Aceh cattle which is useful database for conducting conservation programme. The whole blood samples were collected (8 samples for D-loop analysis) from four locations which were Aceh Besar, Pidie, North Aceh regencies and Banda Aceh city. Out group whole blood samples were collected from two samples from Bali cattles (Bali Island), Madura cattle (Madura Island), Pesisir cattle (West Sumatera) respectively and one sample from PO cattle (West Java). Amplification of D-loop sequences of mtDNA with BIDLF and BIDLR primary have PCR product 980 bp. The Data were analyzed using Squint 1.02 and MEGA 4.0 programme. Result of analysis indicate that Aceh cattle have nearer relationship with zebu and there is items inset of genetik Bali cattle (Bos javanicus) at the end sequences start ke-354 situs up to 483, so that the origin Aceh cattle was from Bos indicus which have hybridization with Bos javanicus.